A Dominant Narrative in Economics?: Preservice Teachers and Pluralism in a Social Studies Methods Class - Neil Graham Shanks (Journal of Social Science Education, 2018)
Purpose: The purpose of this study is to evaluate one effort to challenge the problematic assumptions of the dominant narrative of neoclassical economics within a teacher preparation program that focuses on addressing dominant narratives throughout the social studies curriculum.